Alterations in metabolic pathways: a bridge between aging and weaker innate immune response - Saleh, Zahra; Mirzazadeh, Sara; Mirzaei, Fatemeh; Heidarnejad, Kamran; Meri, Seppo; Kalantar, Kurosh (Frontiers in Aging, 2024)
Aging is a time-dependent progressive physiological process, which results in impaired immune system function. Age-related changes in immune function increase the susceptibility to many diseases such as infections, autoimmune diseases, and cancer. Different metabolic pathways including glycolysis, tricarboxylic acid cycle, amino acid metabolism, pentose phosphate pathway, fatty acid oxidation and fatty acid synthesis regulate the development, differentiation, and response of adaptive and innate immune cells. During aging all these pathways change in the immune cells. In addition to the changes in metabolic pathways, the function and structure of mitochondria also have changed in the immune cells. Thereby, we will review changes in the metabolism of different innate immune cells during the aging process.